A brief online writing intervention improves positive body image in adults living with dermatological conditions - Adkins, Kate V.; Overton, Paul G.; Thompson, Andrew R. (Frontiers in Medicine, 2022)
Dermatological conditions can affect how individuals feel about their bodies. This research therefore seeks to evaluate the potential for a brief writing intervention, focused on body functionality, to improve body image in adults living with a range of dermatological conditions. As part of a parallel Radomised Controlled Trial, 451 adults living with a dermatological condition were randomized to either three functionality-based writing tasks or three creative writing tasks (control). Of these, 155 participants completed pre- and post-intervention measures of body appreciation, functionality appreciation, appearance anxiety, skin-related shame, and skin-related quality-of-life. For participants with relatively low or mid-range scores on baseline body appreciation and functionality appreciation, there were medium-to-large positive effects of the intervention. Effects were smaller, with all but-one remaining significant, at one-month follow up and in Intention-To-Treat analyses. No between-group effects of the intervention were found for measures of appearance anxiety, skin-related shame, and skin-related quality-of-life. These findings suggest that a one-week writing intervention has the potential to improve positive aspects of body image, but not appearance- and skin-related distress in adults living with a dermatological condition.